Transforming Nigeria's Agricultural Value Chains: The Role of Digital Platforms in Market Access and Price Transparency (UNIZIK Journal of Marketing, 2024)
The agricultural industry has long grappled with the issue of unfair pricing, which affects both farmers and the entire value chain. Farmers have often suffered from the discrepancies in pricing, caused by intermediaries and end-users. This recurring problem has led to significant revenue losses for farmers, posing a pressing challenge for the agricultural sector. This study examines how digital platforms improve market connections and price transparency in Nigeria's agricultural value chains. The study was anchored on three objectives, which were to: investigate the mechanisms through which digital platforms enhance price transparency in agricultural value chains; assess the extent to which digital platforms contribute to improving the efficiency of agricultural value chains; and explore how the adoption of digital platforms in agricultural markets influences gender dynamics and social inclusion. A positivism research approach, quantitative research strategy was adopted. Online survey was used to solicit responses from 150 farmers residing in both Lagos and Ogun States respectively which were randomly selected.  It was revealed from the analysis that the adoption of digital platforms significantly enhanced price transparency. Furthermore, it was revealed that digital platforms bring to value chains numerous efficiencies such as: streamlining transactions, reducing intermediaries, and optimizing the flow of goods and information. Lastly, it was established that digital platforms contribute to fostering gender equity by enhancing women's participation, decision-making power, and access to market opportunities. It was concluded that digital platforms substantially impact agricultural value chains, focusing on price transparency enhancement, operational efficiency improvement, and gender dynamics transformation.
Keywords: Market Connections; Transparency of Prices; Agriculture, Value Chains; Digital Platforms